Financial incentives and moral distress in Australian audiologists and audiometrists. (March 2023) - Simpson, Andrea; Fawcett, Meg; McLeod, Lily; Lin, Jennifer; Tuncer, Selda; Sarkic, Bojana
Introduction: Financial incentive schemes have been commonly used by the hearing aid industry as a way of encouraging device sales. These schemes can lead to a conflict of interest as the hearing device dispenser is torn between personal reward over the best interests of their client. This conflict of interest has the potential for the dispenser to develop "moral distress", a negative state of mind when an individual's ethical values contrast with those of the employing organization. The purpose of this study was to investigate if there was a relationship between financial incentives and moral distress in Australian audiologists and audiometrists. Methods: An online survey was distributed to all members of Audiology Australia and the Australian College of Audiology via email. Participants rated their perceived moral distress from 0 to 10 on the Moral Distress Thermometer and answered four questions about financial incentives in their respective workplace. Results: A total of 65 participants, 42 females and 23 males, completed the online survey. A quarter of participants rated their moral distress corresponding to levels of uncomfortable or above. A statistically significant association was found between financial incentives, sales target setting, and higher perceived moral distress in participants. Conclusions: For our sample, the implementation of financial incentives created ethical challenges for practicing audiologists and audiometrists. Modifications to employee rewards programs as well as a regulation of device sales are recommended.